Rare or orphan diseases. A review study - Ener Mantilla Horna; Jóhel Osorio Fernández (Medisur)
Rare or orphan diseases represent a significant challenge to modern medicine due to their low prevalence and lack of effective treatments. This review analyzes the current literature on these diseases, highlighting the importance of research, early diagnosis, and the development of therapies. There are more than 6,000 rare diseases, each with different symptoms and trajectories, and a prevalence of less than 1 case per 2,000 people. Most of these diseases are chronic, progressive, life-threatening, and disabling. Together, they affect 300 million people worldwide. Due to the rarity of each condition, patients often lack information about the evolution and treatment of their disease, and geographic dispersion makes it difficult to access appropriate care and contact other patients with the same disease. This poses a challenge for both patients and healthcare professionals, as a patient with a chronic rare or orphan disease is often unique in the primary care setting. Mental health care for patients with rare or orphan diseases is essential to improve their quality of life. A comprehensive approach that includes psychological support, education and research can help address the unique challenges faced by these patients and their families.